Preparation method of modified MXene / epoxy resin composite anticorrosive paint
By modifying the combination of MXene and epoxy resin, a densified structure and conductive properties are formed, which solves the problems of insufficient anticorrosion performance and poor dispersion of nanoparticles of epoxy resin coatings, and achieves efficient anticorrosion performance and coating stability improvement.
Patent Information
- Application Number
- CN202411259554.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
The existing epoxy resin coatings have volatile compounds that are harmful to the environment and human health. They are prone to holes or microcracks during the coating curing process, which reduces anti-corrosion performance. The nanoparticles such as PANI have poor solubility and poor dispersion, resulting in corrosive media. Through, the conductivity decreases.
By mixing L-ascorbate modified MXene with epoxy resin, a dense structure with layers of stacked layers is formed, reducing pores after solvent volatilization, increasing the corrosive medium transmission path, using the conductive properties of MXene to enhance corrosion resistance, and through slippage and rearrange the overall strength and toughness of the coating.
It significantly improves the corrosion resistance of the composite epoxy coating, forms a thick protective film, enhances the physical barrier on the metal surface, delays the corrosion rate, improves the hardness, impact resistance and flexibility of the coating, and avoids the oxidation of nanofillers. and reunite.
Smart Images

Figure CN119119825A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of anti-corrosion coating materials, and specifically relates to a method for preparing a modified MXene / epoxy resin composite anti-corrosion coating. Background Art
[0002] Corrosion is one of the main failure modes of metal materials, causing huge economic losses and safety hazards every year. Waterborne epoxy resin (EP) is widely used as an anti-corrosion coating matrix due to its advantages such as corrosion resistance, chemical resistance and strong adhesion to heterogeneous substrates. However, epoxy resin coatings still have some disadvantages, such as containing a certain percentage of volatile compounds (VOCs), which are extremely harmful to the environment and human health; during the coating curing process, cross-linking curing and solvent evaporation make the coating prone to defects such as holes or microcracks, which are corrosive media (such as H2O, O2, Cl - ) provides a channel for rapid diffusion to the metal matrix, thereby reducing the anti-corrosion performance of the coating. Therefore, the research and preparation of environmentally friendly epoxy resin coatings with long durability and higher anti-corrosion performance has become a research hotspot for anti-corrosion coatings.
[0003] Studies have shown that the introduction of functional nanoparticles into epoxy resin coatings can enhance the shielding effect or construct a super-hydrophobic surface, which not only prevents the occurrence of corrosion, but also prolongs the service life of the coating. For example, patent CN112680066A PANI / single-layer MoS2 modified epoxy composite anti-corrosion coating and its preparation method discloses a coating that uses nanoparticles to improve the density of the coating, mainly by shielding corrosive media such as water and oxygen, and anode passivation. However, there are still the following shortcomings and deficiencies: (1) PANI has poor solubility, and has the disadvantages of porosity and low adhesion, which makes it easy for corrosive media to penetrate the pores of PANI, thereby easily leading to the oxidation of nano MoS2; (2) The dispersibility and compatibility between PANI and epoxy resin are poor, and the adhesion of the epoxy anti-corrosion coating doped with PANI is poor; (3) PANI is intercalated between the MoS2 layers, which increases the interlayer spacing between the MoS2 layers, resulting in a decrease in conductivity. The nanofiller cannot quickly transfer electrons to the coating surface, so that the electrons move to the anode, resulting in Fe 3+ Formed in large quantities. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a method for preparing a modified MXene / epoxy resin composite anti-corrosion coating. In this method, MXene is modified by L-sodium ascorbate to improve its dispersibility in epoxy resin, thereby forming a layered densified structure in the epoxy anti-corrosion coating, reducing the pores formed after solvent volatilization, increasing the transmission path of corrosive media, effectively forming a shielding effect, and significantly improving the anti-corrosion performance of the composite epoxy coating.
[0005] The present invention provides a method for preparing a modified MXene / epoxy resin composite anti-corrosion coating, which specifically comprises the following steps:
[0006] (1) mixing a 1-5 mg / mL sodium L-ascorbate (NaAsc) solution with a 1-5 mg / mL MXene dispersion, subjecting the mixture to a hybridization reaction under magnetic stirring for 1-10 h at room temperature, ultrasonically treating the mixture for 10-60 min after the reaction, freeze-drying the mixture for 24-48 h, and grinding the mixture into powder to obtain NaAsc / MXene powder;
[0007] (2) Acetone is added to the epoxy resin for dilution to obtain an epoxy resin solution; NaAsc / MXene powder is added to N,N-dimethylformamide (DMF) to obtain a NaAsc / MXene dispersion; the NaAsc / MXene dispersion is then added to the epoxy resin solution and stirred evenly; glycidyl methacrylate, a leveling agent and 650 low molecular weight polyamide are then added, and stirring is continued to obtain a composite anti-corrosion coating.
[0008] In one embodiment of the present invention, in step (1), the preparation method of MXene dispersion is:
[0009] Prepare a hydrochloric acid solution with a concentration of 1-10 mol / L, take 20-40 mL, add 1-5 g LiF, stir at 30-50 ° C for 30-60 min, and then add 1-5 g Ti3AlC2 to react. After the reaction is completed, wash with deionized water until the solution pH is greater than 6, then centrifuge and pour out the supernatant, add deionized water and ultrasonicate, after the ultrasonication, centrifuge again to pour out the supernatant, add deionized water, and then centrifuge. The upper turbid liquid obtained is the MXene dispersion.
[0010] In one embodiment of the present invention, in step (1), the mass ratio of the sodium L-ascorbate solution to the MXene dispersion is (1-10):1.
[0011] In one embodiment of the present invention, in step (2), the epoxy resin is bisphenol A epoxy resin.
[0012] In one embodiment of the present invention, in step (2), the acetone is 10-40% of the mass of the epoxy resin.
[0013] In one embodiment of the present invention, in step (2), the NaAsc / MXene powder is 1 to 3% of the mass of the epoxy resin.
[0014] In one embodiment of the present invention, in step (2), the concentration of the NaAsc / MXene dispersion is 1 to 10 mg / mL.
[0015] In one embodiment of the present invention, in step (2), the leveling agent is an organosilicon surfactant.
[0016] In one embodiment of the present invention, in step (2), the mass ratio of epoxy resin, glycidyl methacrylate, leveling agent and 650 low molecular weight polyamide is: (4-6): (0.1-1): (1-2): (1-3).
[0017] The present invention provides a modified MXene / epoxy resin composite anti-corrosion coating prepared by the above method.
[0018] [Beneficial Effects]
[0019] (1) The present invention uses MXene and epoxy resin to form a composite material, which can form a protective layer on the metal surface and enhance the anti-corrosion ability through electrochemical anode reaction; the excellent conductive property of MXene is used to transfer the electrons lost by the metal to the coating surface, which can slow down the corrosion rate of the metal;
[0020] (2) The modification of MXene by sodium L-ascorbate can form an orderly stack between MXene nanosheets, thereby increasing its surface area and enhancing its stability, which increases the migration speed of electrons on the surface of the material. At the same time, MXene modified by sodium L-ascorbate has good compatibility with epoxy resin and can be stacked layer by layer in the coating to form an orderly structure, thereby effectively enhancing the anti-corrosion performance of the composite epoxy coating; when MXene reaches a certain concentration, it will form a thick protective film on the surface of the coating, creating a good physical barrier on the metal surface and improving the anti-corrosion performance of the material;
[0021] (3) The modified MXene / epoxy resin composite epoxy anti-corrosion coating prepared by the present invention can effectively fill the micropores in the coating to form a densified structure due to the addition of MXene nanosheets, and can also effectively enhance the overall strength and toughness of the coating; when the composite epoxy coating is subjected to impact or bending, the MXene nanosheets can slip and rearrange, which can effectively absorb and disperse stress and avoid stress concentration leading to cracking of the coating; at the same time, the addition of MXene nanosheets makes the coating ductile, so that the coating can withstand large deformation and has good flexibility;
[0022] (4) The present invention modifies the nanofiller by using an antioxidant to prevent the nanofiller from being oxidized due to long-term contact with corrosive media, and at the same time prevents the nanofiller from agglomerating, so that the nanofiller has good dispersibility in the epoxy resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1Schematic diagram of the anti-corrosion effect of the modified MXene / epoxy resin composite epoxy anti-corrosion coating in an embodiment of the present invention;
[0024] Figure 2 The following are scanning electron microscope images of modified MXene composite epoxy coatings with different contents: (a) pure EP (Comparative Example 1); (b) EP-MXene1.0 (Example 1); (c) EP-MXene1.5 (Example 2); (d) EP-MXene2.0 (Example 3); (e) EP-MXene2.5 (Example 4); (f) EP-MXene3.0 (Example 5);
[0025] Figure 3 The flexibility test diagram of modified MXene composite epoxy coatings with different contents: (a) pure EP (Comparative Example 1); (b) EP-MXene0.5 (Comparative Example 2); (c) EP-MXene1.0 (Example 1); (d) EP-MXene1.5 (Example 2); (e) EP-MXene2.0 (Example 3); (f) EP-MXene2.5 (Example 4);
[0026] Figure 4 It is a Tafel polarization curve diagram of modified MXene composite epoxy coatings with different contents in Examples 1 to 5 and Comparative Examples 1 to 3;
[0027] Figure 5 It is the electrochemical impedance diagram of modified MXene composite epoxy coatings with different contents in Examples 1 to 5 and Comparative Examples 1 to 3 immersed in 3.5% NaCl solution for 24 hours. DETAILED DESCRIPTION
[0028] The leveling agent used in the embodiment of the present invention is a silicone surfactant purchased from BYK Additives (Shanghai) Co., Ltd., BYK-346 leveling agent.
[0029] Flexibility test: Refer to GB / T1731-2020 paint film and putty film flexibility test method to test the flexibility of the coating.
[0030] Impact resistance test: refer to GB / T20624.1-2006 paint and varnish rapid deformation (impact resistance) test.
[0031] Adhesion test: Test the adhesion of the coating with reference to the cross-cut test of paint and varnish film in GB / T9286-1998. Grade 0: The cut edge is completely smooth, and no grid falls off; Grade 1: A little coating falls off at the intersection of the cuts, but the affected cross-cut area cannot be significantly greater than 5%; Grade 2: The coating falls off at the intersection of the cuts and / or along the cut edges, and the affected cross-cut area is significantly greater than 5%, but not significantly greater than 15%; Grade 3: The coating falls off partially or completely in large pieces along the cut edge, and / or partially or completely peels off at different parts of the grid, and the affected cross-cut area is significantly greater than 15%, but not significantly greater than 35%; Grade 4: The coating falls off in large pieces along the cut edge, and / or some squares fall off partially or completely. The affected cross-cut area is significantly greater than 35%, but not significantly greater than 65%; Grade 5: The degree of peeling exceeds Grade 4.
[0032] Hardness test: Refer to GB / T6739-2006 Pencil hardness test standard for paints and varnishes.
[0033] Example 1
[0034] A method for preparing a modified MXene / epoxy resin composite anti-corrosion coating comprises the following steps:
[0035] (1) Prepare a 9 mol / L hydrochloric acid solution, take 30 mL, add 2 g LiF, stir at 40 °C for 30 min, then add 2 g Ti3AlC2 and stir for 24 h. After the reaction is completed, wash with deionized water until the solution pH is > 6, then centrifuge and pour out the supernatant, then add deionized water and ultrasonicate for 2 h. After the ultrasonication, centrifuge at 5000 r / min for 10 min, pour out the supernatant, add 20 mL deionized water, and then centrifuge at 3500 r / min for 5 min. The upper turbid liquid obtained is the MXene dispersion;
[0036] (2) 1 mg / mL sodium L-ascorbate (NaAsc) solution and 5 mg / mL MXene dispersion were mixed in a mass ratio of 4:1, and hybridized under magnetic stirring for 1 h at room temperature. After the reaction, the mixture was ultrasonically treated for 30 min, freeze-dried for 24 h, and ground into powder to obtain NaAsc / MXene powder.
[0037] (3) 5 g of bisphenol A epoxy resin was added to a beaker, and 1 g of acetone was added for dilution to obtain a bisphenol A epoxy resin solution; NaAsc / MXene powder was added to DMF to obtain a NaAsc / MXene dispersion with a concentration of 5 mg / mL, wherein the NaAsc / MXene powder was 1.0% of the mass of the epoxy resin; then the NaAsc / MXene dispersion was added to the bisphenol A epoxy resin solution and stirred for 10 min, followed by adding 0.5 g of glycidyl methacrylate, 1 g of leveling agent (BYK-346 leveling agent), and 2.14 g of 650 low molecular weight polyamide, stirring for 5 min, and finally vacuuming for 5 min to remove bubbles in the coating to obtain a composite anti-corrosion coating (Ep-MXene 1.0 ).
[0038] Example 2
[0039] The difference between this embodiment and embodiment 1 is that the addition amount of NaAsc / MXene powder is 1.5% of the epoxy resin, and the remaining steps are the same as those in embodiment 1 to obtain a composite anticorrosive coating (Ep-MXene 1.5 ).
[0040] Example 3
[0041] The difference between this embodiment and embodiment 1 is that the addition amount of NaAsc / MXene powder is 2.0% of the epoxy resin, and the remaining steps are the same as those in embodiment 1 to obtain a composite anticorrosive coating (Ep-MXene 2.0 ).
[0042] Example 4
[0043] The difference between this embodiment and embodiment 1 is that the addition amount of NaAsc / MXene powder is 2.5% of the epoxy resin, and the remaining steps are the same as those in embodiment 1 to obtain a composite anticorrosive coating (Ep-MXene 2.5 ).
[0044] Example 5
[0045] The difference between this embodiment and embodiment 1 is that the addition amount of NaAsc / MXene powder is 3.0% of the epoxy resin, and the remaining steps are the same as those in embodiment 1 to obtain a composite anticorrosive coating (Ep-MXene 3.0 ).
[0046] Comparative Example 1
[0047] The difference between this comparative example and Example 1 is that the addition amount of NaAsc / MXene powder is 0%, and an epoxy resin anticorrosive coating (Ep) is obtained.
[0048] Comparative Example 2
[0049] The difference between this comparative example and Example 1 is that the addition amount of NaAsc / MXene powder is 0.5% of the epoxy resin, and the remaining steps are the same as those in Example 1 to obtain a composite anticorrosive coating (Ep-MXene 0.5 ).
[0050] Comparative Example 3
[0051] Compared with Example 4, this comparative example is different in that the added MXene is not modified by sodium L-ascorbate, and the remaining steps are the same as those in Example 4.
[0052] The surface of the T52 tinplate sheet was polished with 500-mesh sandpaper, and after polishing, it was cleaned with deionized water and anhydrous ethanol, then wiped clean, and dried for use; the coating prepared in the embodiment and the comparative example was applied to the pre-treated T52 tinplate sheet by an automatic coating machine, and cured in a vacuum oven at 60°C for 24 hours to obtain a composite epoxy coating, and its relevant properties were evaluated.
[0053] Table 1 Test results of embodiments and comparative examples
[0054] Impact resistance (cm) Adhesion(grade) hardness Comparative Example 1 90 0 2B Comparative Example 2 90 0 2B Example 1 95 0 B Example 2 95 0 HB Example 3 95 0 H Example 4 100 0 2H Example 5 100 0 2H Comparative Example 3 95 0 H
[0055] According to the data in Table 1, it can be observed that the increase in the mass fraction of NaAsc / MXene will have a significant effect on the hardness and impact resistance of the coating. Compared with the pure epoxy resin coating (Comparative Example 1), under the same conditions, the NaAsc / MXene and epoxy resin composite coating performs better. When the content of NaAsc / MXene is 0.5%, the hardness of the coating is only 2B due to the uneven distribution caused by the nano-sheet structure of MXene. However, with the increase of MXene content, the hardness of the coating is significantly enhanced, which can be attributed to a uniform MXene protective film formed on the surface of the coating. At the same time, due to the high hardness of MXene itself, it also provides a higher hardness for the coating. In addition, due to the strong adhesion interaction between the epoxy groups rich in epoxy resin and the curing agent, the MXene / epoxy resin composite coating has excellent impact resistance, which increases with the increase of MXene content. This is mainly due to the addition of MXene to improve the toughness of the composite coating. In summary, the coating performance is best when the addition amount of NaAsc / MXene is 2.5%.
[0056] from Figure 2 From the scanning electron microscope images of modified MXene composite epoxy coatings with different contents, it can be seen that the surface of pure epoxy resin anti-corrosion coating has more micropores and cracks, while the surface of the composite epoxy coating with added MXene is smooth and crack-free.
[0057] from Figure 3 It can be seen that cracking occurred at the creases of the pure EP (Comparative Example 1) and EP-MXene0.5 (Comparative Example 2) coatings, while no cracking or peeling occurred at the creases of the other composite epoxy coatings.
[0058] Figure 4 The Tafel polarization curves of modified MXene composite epoxy coatings with different contents are shown in Figure 2. The larger the corrosion potential of the polarization curve, the smaller the corrosion current density, indicating that the anti-corrosion performance is better. Figure 5 The electrochemical impedance diagram of modified MXene composite epoxy coatings with different contents immersed in 3.5% NaCl solution for 24 hours. The higher the value at |Z|f=0.01Hz, the better the anti-corrosion performance of the coating. Compared with Comparative Example 1, the corrosion voltages of Examples 1-5 and Comparative Examples 2-3 have been significantly improved, the corrosion current density has been correspondingly reduced, and the low-frequency impedance modulus has also been significantly increased. Among them, the corrosion current density of Examples 4 and 5 is one order of magnitude lower than that of Comparative Example 1. Compared with Comparative Example 3, the corrosion voltage of Example 4 has been significantly improved, the corrosion current density has been correspondingly reduced, and the low-frequency impedance modulus has also been significantly increased. The MXene of Example 4 can be significantly enhanced by modification with sodium L-ascorbate to enhance the anti-corrosion performance of the coating.
[0059] Table 2 Anticorrosion performance test results of the embodiments and comparative examples
[0060] sample <![CDATA[E corr / V]]> <![CDATA[I corr / ×10 -7 (A·cm -2 )]]> <![CDATA[ / Z / corr / ×10 -8 (Ω·cm -2 )]]> Comparative Example 1 -1.126 7.069 0.51 Comparative Example 2 -1.018 3.212 1.14 Example 1 -0.958 1.617 0.75 Example 2 -0.923 1.296 2.32 Example 3 -0.874 1.636 3.11 Example 4 -0.731 0.440 7.91 Example 5 -0.717 0.533 8.87 Comparative Example 3 -0.902 1.059 3.72
[0061] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a composite anti-corrosion coating, characterized in that: The steps include: (1) mixing and reacting a sodium L-ascorbate solution and a MXene dispersion, and then sonicating, freeze-drying, and grinding after the reaction to obtain a sodium L-ascorbate / MXene powder; (2) Acetone is added to the epoxy resin for dilution to obtain an epoxy resin solution; L-sodium ascorbate / MXene powder is added to N,N-dimethylformamide to obtain an L-sodium ascorbate / MXene dispersion; the L-sodium ascorbate / MXene dispersion is then added to the epoxy resin solution; and finally, glycidyl methacrylate, a leveling agent, and 650 low molecular weight polyamide are added and stirred to obtain a modified MXene / epoxy resin composite anti-corrosion coating.
2. The method for preparing a composite anti-corrosion coating according to claim 1, characterized in that: In step (1), the concentration of the sodium L-ascorbate solution is 1 to 5 mg / mL; the concentration of the MXene dispersion is 1 to 5 mg / mL.
3. The method for preparing a composite anti-corrosion coating according to claim 1, characterized in that: In step (1), the mass ratio of the sodium L-ascorbate solution to the MXene dispersion is 1 to 10:
1.
4. The method for preparing a composite anticorrosive coating according to claim 1, characterized in that: In step (1), the preparation method of the MXene dispersion is as follows: prepare a hydrochloric acid solution with a concentration of 1 to 10 mol / L, take 20 to 40 mL, add 1 to 5 g LiF, stir at 30 to 50 ° C, and then add 1 to 5 g Ti3AlC2 to react. After the reaction is completed, wash with deionized water until the solution pH is greater than 6, then centrifuge and pour out the supernatant, then add deionized water and ultrasonicate, after the ultrasonication is completed, centrifuge and pour out the supernatant, then add deionized water, and then centrifuge to obtain the upper turbid liquid, which is the MXene dispersion.
5. The method for preparing a composite anti-corrosion coating according to claim 1, characterized in that: In step (2), the epoxy resin is bisphenol A epoxy resin; and the leveling agent is an organosilicon surfactant.
6. The method for preparing a composite anticorrosive coating according to claim 1, characterized in that: In step (2), the acetone is 10 to 40% of the mass of the epoxy resin.
7. The method for preparing a composite anticorrosive coating according to claim 1, characterized in that: In step (2), the amount of sodium L-ascorbate / MXene powder used is 1 to 3% of the mass of the epoxy resin.
8. The method for preparing a composite anti-corrosion coating according to claim 1, characterized in that: In step (2), the mass ratio of epoxy resin, glycidyl methacrylate, leveling agent and 650 low molecular weight polyamide is (4-6):(0.1-1):(1-2):(1-3).
9. The method for preparing a composite anticorrosive coating according to claim 1, characterized in that: In step (2), the concentration of the sodium L-ascorbate / MXene dispersion is 1 to 10 mg / mL.
10. A modified MXene / epoxy resin composite anti-corrosion coating prepared by the method of any one of claims 1 to 9.
Citation Information
Patent Citations
Sodium ascorbate surface modified titanium carbon MXene functional ink and humidity sensor
CN115266829A
MXene modified epoxy anticorrosive paint and preparation method thereof
CN115926581A
Method for improving corrosion resistance of vinyl ester resin
US11692103B1
Cited By
Fireproof and stain-resistant composite coating and preparation method thereof
CN119708954A
